2016
DOI: 10.1161/hypertensionaha.115.06667
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Cardiovascular Function in Normal Pregnancy

Abstract: Abstract-The aim of this study was to investigate cardiac functional status in pregnancy using a comprehensive approach taking into account the simultaneous changes in loading and geometry, as well as maternal age and anthropometric indices. This was a prospective cross-sectional study of 559 nulliparous pregnant women assessed at 4 time points during pregnancy and at 1 year postpartum. All women underwent conventional echocardiography and tissue Doppler velocities and strain rate analysis at multiple cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
89
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(105 citation statements)
references
References 39 publications
12
89
3
1
Order By: Relevance
“…To assess stroke volume Savu et al [2] used the Doppler technique, while we used the biplane Simpson method for the calculation. Surprisingly, unlike other studies, which reported both RA and RV enlargement [1,14,15], we observed only mild RA dilatation in group A ( Table 4). The reason why we did not observe RV enlargement remains unclear and requires further examination.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…To assess stroke volume Savu et al [2] used the Doppler technique, while we used the biplane Simpson method for the calculation. Surprisingly, unlike other studies, which reported both RA and RV enlargement [1,14,15], we observed only mild RA dilatation in group A ( Table 4). The reason why we did not observe RV enlargement remains unclear and requires further examination.…”
Section: Discussioncontrasting
confidence: 99%
“…Most of the haemodynamic changes and subsequent cardiac remodelling observed in all women in our study are characteristic of normal pregnancy and are consistent with findings from other studies [1,2,[10][11][12][13][14]. This applies to an increase in heart rate, LV stroke volume, and LVCO, and to a decrease in SVR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even in normal pregnancy, myocardial and ventricular function decline after the second trimester (187). The findings of a drop in stroke volume index, impaired myocardial relaxation with diastolic dysfunction, and eccentric remodeling at term are suggestive of cardiovascular maladaptation to the volume overload in some apparently normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…We found an increase in NRL and MPV during pregnancy, supporting this theory of increased inflammatory response at the end of pregnancy. A recent paper by Melchiorre et al (14) describes an increase in total vascular resistance and endsystolic wall stress at term as a consequence of the persistent overload of volume during pregnancy. During normal pregnancy, there is an overt systemic vasodilatation at all levels of the vascular tree, resulting in a higher shear stress, possibly compromising microvascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%